Eksistensi Pondok Pesantren Berbasis Tarekat dalam Era Global dan Digital - Samsulbassar , Agus (Program Pascasarjana Universitas Ibrahimy, 2018)
Pondok Pesantren Suryalaya is one of Islamic Boarding school in Indonesia. It was oldest Sufistic Education Institution which gave the essential contribution to educate nation and improved the quality of its life. There is assumption that sufi’s education can face all the stuff of the global and digital process. This reseach the author explained there were some reasons that was Sufistic Education Institution have best influence in Islamic Education, especially in internalization and identification of Islam to all nation to close to Allah SWT.